Potret Keuntungan Pedagang Buah Berbasis Nilai Budaya Islam di Gorontalo - Mohamad Anwar Thalib; Anggun Fitra N. Mohamad; Cindriyati Ibrahim; Maryam S. Ahaya; Amelia Ijini (Program Studi Agribisnis, 2022)
ABSTRACT This research departs from the problem of the lack of research on accounting based on local wisdom compared to modern accounting research. This situation makes local accounting increasingly marginalized and even has the opportunity to disappear and be replaced by modern accounting. This study aims to understand the practice of profit accounting based on Islamic cultural values in Gorontalo. The method used is qualitative with four informants who are fruit traders. The data analysis method used is Miles and Huberman model data analysis. The results show that fruit traders experienced a decline in profits due to the COVID-19 pandemicc. Profits earned from trading fruit are used to meet personal needs and share with people in need in the form of alms. Profit sharing is driven by their awareness of